Pengembangan Media Google Site dalam Bimbingan Klasikal di SMAN 1 Sampung - Setyawan, Bambang (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2019)
This development aims to produce a classical guidance media that can be accessed through smartphones and meets the elements of eligibility through expert user trials, and field trials. In addition, through this development activity, it is also expected to provide positive internet content. The development model adapts the ASSURE concept, namely through steps: analyzing students' characteristics, standards and goals, choosing strategy-technology-media and materials, using technology, media and materials, requiring student participation, evaluating and revising. The feasibility test, based on the ACTIONS concept, produces a score of 317 with a maximum score of 340, the eligibility level reaches 93%. While from the field test conducted in XII Science 1 with the main focus of observation on the active behavior, the total score is 1417 with a maximum score of 1450, the level of activity is 97.72%. Based on the results of expert tests by certified BK teachers and data from field test results, it was found that the website with google site was accepted and suitable as a classical guidance media. To get wider benefits it is recommended to arrange media for other material content.